Determining management strategies for the Sarikum Nature Protection Area - Öztürk, Sevgi (Springer Science and Business Media LLC, 2015)
In recent years, many environmental problems have become important factors in promoting the economic need to develop tourist activity: climate change such as energy wars, increasing hunger and aridity, population increases in urban areas, excessive and unthinking use of natural resources, difficult international relations, economic competition, and increasing environmental stress. Trends in global tourism have changed with changes in culture and our attitude to nature. Changes in both the profile and consumption patterns of tourists have called for the need to balance the use of natural and cultural assets with the need to adequately protect them. In this study, the Sarikum Nature Protection Area (SNPA) was selected as a case study because of its significance as a Turkish wetland area and the variety of different ecosystems coexisting within it. The study focussed on management strategies, but also provides a broader strategy for an area that currently has no management plan. Strengths and weaknesses, opportunities and threats (SWOT) analyses of the area were gathered and analyzed using R'WOT analysis (ranking + SWOT), a multi-criteria assessment method, in order to determine strategies, obtain the participation of interest groups, and assess their opinions and attitudes. The analysis showed the following: the rich biological diversity and the existence of endemic species were the reserve's most significant strength; the presence of natural areas in surrounding regions was the most significant opportunity; the shortage of infrastructure and lack of legal regulation of ecotourism was the most significant weakness; and the lack of a management plan was the most immediate threat.
Keywords: Conservation of Natural Resources; Turkey; Climate Change; Culture; Biodiversity; Management, Monitoring, Policy and Law; Pollution; Article; Environmental Science(all); Public Opinion; Wetlands; Ecosystem; Environmental Monitoring; 2. Zero hunger; 15. Life on land; 13. Climate action; 11. Sustainability; 8. Economic growth